Evaluating Instructional Strategy Effectiveness of Physical Education Teachers in Implementing the Independent Curriculum - Kamarudin Kamarudin; Hendra Iskandar; Moh Tris Maulana Daipaha; Muh Saldi; Muhamad Usba (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: The implementation of Indonesia’s Independent Curriculum places strong emphasis on student-centered, project-based, and differentiated learning, including in Physical Education, Sports, and Health (PJOK), which plays a vital role in students’ holistic development. This study aims to evaluate the extent to which PJOK teaching strategies aligned with the Independent Curriculum are implemented in five elementary schools in Palu City Methodology: A quantitative descriptive research design was employed, integrating questionnaire data, classroom observations, and document analysis to obtain a comprehensive picture of instructional practices. The participants consisted of 15 PJOK teachers from five public elementary schools, with data collected using a four-point Likert-scale questionnaire to capture teachers’ perceptions and self-reported practices. Main Findings: The findings indicate that PJOK teachers have largely adopted the Independent Curriculum principles, particularly in planning, assessment, and participation in training programs, which achieved high performance levels. Nevertheless, persistent challenges were identified in the utilization of learning media, limited infrastructure, and time constraints, which restricted the optimal implementation of innovative PJOK learning activities. Novelty/Originality of this study: The novelty of this study lies in its focused empirical examination of PJOK within the Independent Curriculum framework, a subject area that remains underrepresented in curriculum implementation research. By highlighting contextual disparities and practical constraints, this study provides evidence-based insights to inform policy decisions, school leadership strategies, and targeted professional development to strengthen PJOK instruction in primary education.